Determinants of early childhood morbidity and proper treatment responses in Vietnam: results from the Multiple Indicator Cluster Surveys, 2000-2011 - Hwa-Young Lee; Nguyen Van Huy; Sugy Choi (Taylor & Francis Group, 2016)
Background: Despite significant achievements in health indicators during previous decades, Vietnam lags behind other developing countries in reducing common early childhood illnesses, such as diarrhea and respiratory infections. To date, there has been little research into factors that contribute to the prevalence and treatment of childhood morbidity in Vietnam. Objective: This study examines the determinants of diarrhea and 'illness with a cough' and treatments for each of the conditions among young children in Vietnam, and describes trends over time. Design: Data from the Vietnam Multiple Indicator Cluster Surveys in 2000, 2006, and 2011 were used. Multivariable logistic regressions were undertaken to investigate factors associated with these childhood illnesses and proper treatment patterns. Results: Between 2000 and 2011, the prevalence of diarrhea among children under the age of five declined from 11 to 7%, while having illness with a cough increased to 40% in 2011 after falling from 69 to 28% between 2000 and 2006. During the same period, the prevalence of oral rehydration therapy (ORT) for treating diarrhea increased from 13 to 46%, whereas the rate of seeking formal treatment for illnesses with a cough fell from 24 to 7%. Multivariable models indicated that children who were older than 2 years (odds ration [OR]: 0.44, 95% confidence interval [CI]: 0.37-0.53, p<0.001), male (OR: 1.21, 95% CI: 0.64-2.37, p<0.05), living in rural areas (OR: 1.28, 95% CI: 1.00-1.64, p<0.05), or of Kinh ethnicity (OR: 0.70, 95% CI: 0.56-0.87, p<0.01) were more likely to suffer from diarrhea. Ethnic differences and higher household wealth were factors significantly associated with having illness with a cough. In particular, the effect of level of wealth on illness with a cough varied in each wave. Mothers with higher levels of education had higher odds of seeking ORT compared with mothers with the lowest level of education. Seeking formal treatment for children who have illness with a cough was associated with being in a household in the richest wealth quintile (OR: 0.56, 95% CI: 0.34-0.91, p<0.05). Conclusions: This study demonstrates the importance of identifying different risk factors for these two illnesses and also factors associated with healthcare-seeking behaviors in order to reduce the burden of childhood morbidity in Vietnam. Policies aimed at tackling childhood morbidities should include comprehensive strategies that impact on socioeconomic and environmental factors.